Characteristics and mechanism of winter marine heatwaves in the cold tongue region of the South China Sea - Meng, Linxi; Yan, Yunwei; Zhang, Lei; Xing, Wen; Yu, Yi; Xing, Xiaogang (Frontiers in Marine Science, 2024)
Marine Heatwaves (MHWs) are persistent anomalous sea surface temperature warming events that can affect the marine ecological environment and ecosystems. Here, we study the winter MHWs in the cold tongue region of the South China Sea (SCS) from 1982 to 2022. Our results show that the winter MHWs in the cold tongue region have the strongest cumulative intensity in the SCS, exceeding 45°C·day/time. These strong MHWs are due to their high mean intensity and long duration. Significant interannual variations are observed in these MHWs, with extreme MHW events occurring in the El Niño winters of 97/98 and 15/16. By employing a mixed layer heat budget analysis, we reveal that the extreme MHW event in the winter of 97/98 is caused primarily by the surface heat flux term, and secondarily by the vertical entrainment term. While the 15/16 extreme event is caused by a combination of the surface heat flux term, the vertical entrainment term and the horizontal advection term.